Demand response for chemical manufacturing using Economic MPC - Mendoza-Serrano, David I.; Chmielewski, Donald J. (2013 American Control Conference, 2013)
The notion of demand response in electric power systems is to use time varying electricity price structures to encourage consumers to track generation availability. Specifically, when available generation is low, either due to high demand or a lack of renewable sources, an increase in electricity rates is intended to encourage smart grid participants to reduce consumption. Similarly, when on-line generation is higher than demand, smart grid participants may benefit from low electricity rates. While many think of smart grid participants as residential consumers, the commercial building and industrial sectors will likely result in a higher grid impact to implementation cost ratio. In this work we investigate potential demand response mechanisms from the chemical manufacturing industry. It will be shown that depending on the type of upgrade hardware selected the smart grid operating policy will either be an application of Real-Time Optimization (RTO) or Economic Model Predictive Control (EMPC). In the case of EMPC the impact of prediction horizon size will be highlighted.